2010
DOI: 10.1002/esp.1949
|View full text |Cite
|
Sign up to set email alerts
|

Coupling mechanisms in double sandbar systems. Part 2: impact on alongshore variability of inner‐bar rip channels

Abstract: Double sandbar systems are common morphological features along sandy, wave-dominated, micro-to meso-tidal coastlines. In the companion paper, we demonstrated how various alongshore inner-bar rip-channel patterns can develop through morphological coupling to an alongshore-variable outer bar. The simulated coupling patterns are, however, scarcely observed in the fi eld. Instead, inner-bar rip channels more often possess remarkably smaller and more variable alongshore length scales, suggesting that coupling mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…The general fi eld observation that inner-bar rip channels are more irregularly spaced than outer-bar crescents suggests that morphological coupling may be more important to understanding and predicting the evolution of inner-bar rip channels than previously envisaged. This issue is explored in the companion paper (Castelle et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The general fi eld observation that inner-bar rip channels are more irregularly spaced than outer-bar crescents suggests that morphological coupling may be more important to understanding and predicting the evolution of inner-bar rip channels than previously envisaged. This issue is explored in the companion paper (Castelle et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…This enables both the detection of the dominant spatial modes of variability and how these modes vary in space. As in some previous wavelet applications to sandbar data [e.g., Ruessink et al , 2007; Castelle et al , 2010b], we used the Morlet wavelet ψ 0 because of its good localization characteristics in both the space and frequency domains. In all results below, the term wavelength refers to the Fourier wavelength λ equivalent to the wavelet scale s. We determined the statistical significance of W n z ( s ) against synthetic red noise series, as detailed by Torrence and Compo [1998].…”
Section: Methodsmentioning
confidence: 99%
“…The morphological evolution of the inner bar, therefore, is driven by a mixture of self‐organization and outer‐inner bar coupling mechanisms [ Castelle et al , , ]. Although morphological coupling between two sandbars suggests a reciprocal influence, observations [ Ruessink et al ., ] and modeling results [ Castelle et al , , ; Thiébot et al , ] indicated that the inner‐bar morphology does not affect the outer‐bar morphodynamics.…”
Section: Introductionmentioning
confidence: 99%